Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.actbio.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods of fatigue testing bone cement

Abstract: Two different methods have been used to fatigue test four bone cements. Each method has been used previously, but the results have not been compared. One method tests at least 10 samples over a single stress range in tension only and uses Weibull analysis to calculate the median number of cycles to failure and the Weibull modulus. The second test regime uses fewer specimens at various stress levels tested in fully reversed tension-compression, and generates a stress versus number of cycles to failure (S-N) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Dunne et al (2014) point out that while in vitro tension can be a more important factor inducing cement failure than compression, both loading modes occur. Fully reversed tensioncompression stress (mean stress = 0) or tension only stress (mean stress > 0) has been adopted in in vitro studies of fatigue testing bone cement, to imitate better the in vivo fatigue conditions (Tanner et al, 2010). Harper and Bonfield (2000), for example, applied tension-tension fatigue to examine the fatigue properties of various bone cements and reported that "the cements that perform best clinically gave the highest results".…”
Section: Introductionmentioning
confidence: 99%
“…Dunne et al (2014) point out that while in vitro tension can be a more important factor inducing cement failure than compression, both loading modes occur. Fully reversed tensioncompression stress (mean stress = 0) or tension only stress (mean stress > 0) has been adopted in in vitro studies of fatigue testing bone cement, to imitate better the in vivo fatigue conditions (Tanner et al, 2010). Harper and Bonfield (2000), for example, applied tension-tension fatigue to examine the fatigue properties of various bone cements and reported that "the cements that perform best clinically gave the highest results".…”
Section: Introductionmentioning
confidence: 99%
“…The cement dough was then injected into a four-celled silicone mold, with internal configuration and dimensions of a solid cylindrical dog-bone (overall nominal total length = 62.0 mm; diameter of each grip end = 8.5 mm; length of each grip end = 18.0 mm; diameter of central reduced zone = 5.0 mm; length of central reduced Tanner et al [55] zone = 10.0 mm) [6]. All the steps used in the preparation, and aging of the specimens were as stipulated in the relevant testing standard, namely,ASTM F2118-10 [6].…”
Section: Fatigue Life Testing and Estimation Of Fatigue Limitmentioning
confidence: 99%
“…A review paper by Lewis [4] examined the "intrinsic" and "extrinsic" factors that can affect the measured fatigue performance of bone cement, concluded that there are "only a few areas of agreement" and "many areas of disagreement". The effects of specimen preparation variables (cross section shape and surface production technique) on fatigue behaviour at a specific constant-amplitude stress have been examined in previous studies considering the influence of specimen shape in tension-compression only [5], surface preparation method in tension-tension only [6] or the effects of both configuration and fabrication methods in tension-compression [7,8] and tension-tension loading [8,9]. Due to testing at only one stress amplitude, the fatigue data has been analysed using Weibull relationships in most of these studies [5,[7][8][9] and only one study [8] has compared two testing methods: tension-only of rectangular moulded specimens at a single stress level versus tension-compression at multiple stress levels of circular machined specimens analysing the results using Weibull and Wöhler approaches, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue life results are compared by the commonly used S-N (Wöhler) analysis (e.g. [8,12,18,19]) as recommended in ASTM F2118-14. Furthermore, it has been reported that fatigue damage accumulation in vivo shows that failure progress is affected by the stress amplitude, thus using a single stress amplitude would be a "misleading measure of durability" [20].…”
Section: Introductionmentioning
confidence: 99%